Characterization of ethanol-induced casein micelle dissociation using a continuous protein monitoring unit - G. Lewis; L.R. Bodinger; F.M. Harte (Journal of Dairy Science, 2022)
ABSTRACT: The effect of ethanol on milk has been shown to be temperature-dependent, with higher ethanol concentrations and temperatures reversibly dissociating casein micelles. This work looked to expand on this knowledge, while also demonstrating the efficiency and precision of a custom-made continuous monitoring unit that combines solutions at defined concentrations and temperatures while measuring various parameters (i.e., absorbance, fluorescence, pressure). Caseins were found to self-associate at moderate ethanol concentrations (i.e., 12–36% vol/vol ethanol); however, they dissociated and remained in the serum at higher ethanol concentrations (≥48% vol/vol) and temperatures (24 and 34°C). Although serum casein content was found to be positively correlated with protein hydrophobicity, the addition of ethanol only increased protein hydrophobicity when the sample was held at high temperatures (34–64°C). Overall, the greatest dissociation of casein micelles was found between 40 and 60% (vol/vol) ethanol concentration at elevated temperatures (≥34°C). At these ethanol concentrations and temperatures, skim milk absorbance was minimized, serum casein content (including β-casein content) was maximized, and protein hydrophobicity reached a relative maximum.